(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1999)
The singular perurbation for boundary problems for linear systems of ordinary differential equations is considered. Under suitable assumptions using generalized inverse matrix the unique asymptotic expansion with boundary function is constructed.